Teaching early anxiety management by healthcare professionals: an experience report (Research, Society and Development, 2021)
Introduction: this experience report is the result of an intervention in Psychoeducation for the early management of anxiety carried out with health professionals in theTeaching-Learning Process in Health Sciences discipline of a Postgraduate Program in Nursing and Health of a State University in the interior of Bahia. Objective: the objective of the intervention was to provide health professionals with fundamental concepts of Psychoeducation in Anxiety Articulated With Healthcare Practices. Methodology: For this purpose, role playing or role-playing method was used as an active teaching methodology. As an evaluative method, the participation of professionals during the intervention. Results and discussions: As pointed out by the theory, the role-playing method proved to be an important methodology for raising awareness and building meaningful learning with health professionals about the early management of anxiety.Conclusion: As it was possible to observe, the teaching of early anxiety management to health professionals through active methodologies such as role playing to understand the importance of psychoeducation proved to be extremely efficient in that it enabled the participants, through the identification of personal experiences with anxiety, the understanding of the importance of its management, as well as the capacity they have to deal with the subject in their health services and other areas of expertise.